Soil Improvement Using Bamboo Leaf Ash and Cement on Triaxial UU Testing - Azana, Shafira Yuli; Rahayu, Wiwik; Sagitaningrum, Fatiyah Hakim; Kabidiyono, Era Agita (ASTONJADRO, 2026)
Soft soils, particularly those classified as low-plasticity silt (ML) according to ASTM D2487, pose considerable challenges in geotechnical engineering due to their low shear strength, high compressibility, and limited bearing capacity. This study evaluates the effectiveness of bamboo leaf ash (BLA), Portland Composite Cement, and their combination as stabilizing agents for ML-type soft soil. Laboratory investigations were conducted to assess changes in physical and mechanical properties, including Atterberg limits, specific gravity, compaction characteristics, and unconsolidated undrained (UU) triaxial shear strength. Four stabilization mixtures were analysed: untreated soil, soil with 10% BLA, soil with 5% cement, and a mixture of soil with 10% BLA and 5% cement. The results indicate that BLA alone enhances the internal friction angle from 11.03° to 38.84°, primarily through physical densification, but reduces cohesion from 64.49 kPa to 46.12 kPa. Cement treatment increases both cohesion 55.38 kPa and the friction angle 49.16° due to hydration and the formation of a cementitious bond. The combination of 10% BLA and 5% cement yielded the highest cohesion 102.59 kPa and a friction angle of 31.79°, highlighting the synergistic effect of pozzolanic reactions between reactive silica in BLA and calcium compounds from cement hydration. The study concludes that the BLA–cement mixture significantly improves the mechanical behaviour of soft silty soil, offering a sustainable and effective alternative to conventional soil stabilization methods, particularly when supported by controlled parameters such as ash fineness, burning temperature, and curing duration.